2003
DOI: 10.1196/annals.1304.009
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacokinetic and Dynamic Studies of Agmatine (Decarboxylated Arginine)

Abstract: Agmatine has been previously proposed to represent a novel neurotransmitter. One of the criteria required to test that hypothesis is that the exogenously administered chemical produces pharmacological effects similar to the physiological effects of the putative neurotransmitter. Since agmatine was first identified in brain, approximately sixty studies of the in vivo effects of exogenously administered agmatine have been reported. Despite the assertion that agmatine functions as a neuromodulator/neurotransmitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
27
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 60 publications
4
27
0
Order By: Relevance
“…Findings from the central effects of agmatine on functional/behavioral parameters in vivo have not been consistent and vary with the route of administration and doses used (see review [18]). The major unanswered issues are the penetration of agmatine into brain and its biological half-life after peripheral injection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from the central effects of agmatine on functional/behavioral parameters in vivo have not been consistent and vary with the route of administration and doses used (see review [18]). The major unanswered issues are the penetration of agmatine into brain and its biological half-life after peripheral injection.…”
Section: Introductionmentioning
confidence: 99%
“…Since all these conditions involve higher glutamate release and excessive NMDA receptor activation, agmatine could be acting by reducing glutamatergic transmission. While the blockade of NMDA receptors by agmatine have been reported in neuronal cells [30], effects on in vivo glutamate release have not been investigated.Findings from the central effects of agmatine on functional/behavioral parameters in vivo have not been consistent and vary with the route of administration and doses used (see review [18]). The major unanswered issues are the penetration of agmatine into brain and its biological half-life after peripheral injection.…”
mentioning
confidence: 99%
“…Furthermore, an agmatinergic blood-brain barrier transport system has yet to be definitively characterized. In support of the proposal that agmatine exerts its effects through a central site of action, a number of studies have applied agmatine through central routes of administration, including intracerebroventricular (for a complete list, see Nguyen et al, 2003) and intrathecal (Fairbanks and Wilcox, 1997;Horvath et al, 1999;Fairbanks et al, 2000;Hou et al, 2003). Although these pharmacological studies provide proof-of-principle for agmatinergic modulation of many centrally mediated plasticity-requiring phenomena, minimal information is available regarding the pharmacokinetics of agmatine in the serum or the CNS.…”
mentioning
confidence: 99%
“…Although these pharmacological studies provide proof-of-principle for agmatinergic modulation of many centrally mediated plasticity-requiring phenomena, minimal information is available regarding the pharmacokinetics of agmatine in the serum or the CNS. Two preliminary studies report mouse spinal cord (Nguyen et al, 2003) and brain (Piletz et al, 2003) recovery of agmatine after systemic administration of agmatine. Piletz et al (2003) also reported a preclinical study of CSF agmatine recovery after systemic administration (30 mg/kg i.v.)…”
mentioning
confidence: 99%
See 1 more Smart Citation